2023
DOI: 10.21203/rs.3.rs-2552558/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leptin receptor gene polymorphisms in patients with post-transplant diabetes mellitus

Abstract: Post-transplant diabetes mellitus (PTDM) is a metabolic complication that often occurs after kidney transplantation. Factors that increase the risk of this complication are currently being researched, including polymorphisms in genes affecting carbohydrate-lipid metabolism. Leptin is a hormone that affects appetite and adipose tissue and plays an important role in regulating insulin secretion as well as glucose and lipid metabolism. The aim of this study was to examine the association between leptin receptor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Similarly, our study demonstrated that the blood glucose of patients carrying *3/*3 was significantly higher than that in the perioperative period. Diabetes after kidney transplantation is common [27]. Our study also demonstrated that patients carrying CYP3A5 *3/*3 had a significant increase in blood glucose 1 month after transplantation, but this did not occur in the *1/*1 and *1/*3 groups.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, our study demonstrated that the blood glucose of patients carrying *3/*3 was significantly higher than that in the perioperative period. Diabetes after kidney transplantation is common [27]. Our study also demonstrated that patients carrying CYP3A5 *3/*3 had a significant increase in blood glucose 1 month after transplantation, but this did not occur in the *1/*1 and *1/*3 groups.…”
Section: Discussionsupporting
confidence: 55%